The rhetoric of violence and sacrifice in fascist Italy : Mussolini, Gadda, Vittorini - Ferrari, Chiara (Toronto Italian studies., 2013)
In this book, Chiara Ferrari interrogates how the rhetoric of sacrifice was used by the Italian fascist regime throughout the interwar years to support its totalitarian project and its vision of an all-encompassing bond between the people and the state.